2008
DOI: 10.1111/j.1572-0241.2008.01838.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Antioxidants, Fruits, and Vegetables and the Risk of Barrett's Esophagus

Abstract: OBJECTIVE The present study evaluated the associations between antioxidants, fruit and vegetable intakes and the risk of Barrett’s esophagus, a potential precursor to esophageal adenocarcinoma. METHODS We conducted a case-control study within the Kaiser Permanente Northern California population. Incident Barrett’s esophagus cases (n=296) were matched to persons with gastroesophageal reflux disease (GERD) (GERD controls, n=308) and to population controls (n=309). Nutrient intake was measured using a validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
4
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 46 publications
4
55
4
1
Order By: Relevance
“…This histological improvement supported disappearance and/ or alleviation of symptoms in these patients. Our finding is in contrast to earlier case-control reports by Kubo et al (2008) and Murphy et al (2010) where the intake of antioxidant supplements assessed by food-frequency questionnaire did not appear to influence the risk of Barrett's esophagus. Kubo reported dietary intake of β-carotene was inversely associated with the risk of BE (adjusted OR=0.48 and 95%CI=026-0.90), while no association was observed for supplement intake (Kubo, 2008).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This histological improvement supported disappearance and/ or alleviation of symptoms in these patients. Our finding is in contrast to earlier case-control reports by Kubo et al (2008) and Murphy et al (2010) where the intake of antioxidant supplements assessed by food-frequency questionnaire did not appear to influence the risk of Barrett's esophagus. Kubo reported dietary intake of β-carotene was inversely associated with the risk of BE (adjusted OR=0.48 and 95%CI=026-0.90), while no association was observed for supplement intake (Kubo, 2008).…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding is in contrast to earlier case-control reports by Kubo et al (2008) and Murphy et al (2010) where the intake of antioxidant supplements assessed by food-frequency questionnaire did not appear to influence the risk of Barrett's esophagus. Kubo reported dietary intake of β-carotene was inversely associated with the risk of BE (adjusted OR=0.48 and 95%CI=026-0.90), while no association was observed for supplement intake (Kubo, 2008). In contrast to this epidemiological study, in our study a specific amount of β-carotene was administered for six-months and endoscopic, histological markers of Barrett's were objectively measured.…”
Section: Discussioncontrasting
confidence: 99%
“…However, subsequent systematic reviews continue to show a protective role of fruits against gastric cancer [9], and both fruits and vegetables against ESCC [10] and EAC [11]. Importantly, given the growing importance of EAC, there is some evidence that the risk of its precursor lesion, Barrett's esophagus, is also inversely related to fruit and vegetable intake [12,13]. A recent study of patients referred for gastroesophageal endoscopy showed that adherence to WCRF guidelines on diet and exercise, previously shown to be protective against gastric and esophageal cancers amongst others [14], was also associated with a lower risk of both Barrett's esophagus and its progression to EAC [15].…”
mentioning
confidence: 99%
“…Quand un OB est diagnostiqué, les facteurs prédictifs reconnus d'évolution vers le cancer sont le sexe masculin, la longueur de l'OB, un régime alimentaire pauvre en fruits et légumes, et riche en graisse, le tabagisme et l'obésité [6][7][8]. Les facteurs protecteurs décrits seraient un régime alimentaire riche en fruits et légumes [9], et de manière étonnante une infection gastrique à Helicobacter pylori [10].…”
Section: Généralitésunclassified